Recurrent Inguinal Hernia in an Elderly Male Patient: A Case Report - Ilmida Husniana (CV. Publikasi Indonesia, 2026)
Inguinal hernia is a medical condition characterized by the protrusion of intra-abdominal organs through a weakness in the abdominal wall in the inguinal region. This condition is more common in men and can lead to serious complications such as incarceration and strangulation if not treated properly. The purpose of this study is to describe the clinical characteristics, risk factors, diagnosis, and management of recurrent inguinal hernia through case reports. The method used was a case study of a 60-year-old male patient presenting with severe pain in the lower right abdomen that radiated to the right scrotum. A physical examination revealed the presence of an irreducible right scrotal herniation. The patient had a history of previous bilateral hernioplasty and risk factors including heavy lifting activities. The diagnosis was established based on anamnesis and physical examination, followed by a herniotomy with mesh insertion. The results indicated that increased intra-abdominal pressure and tissue weakness contributed to the recurrence. In conclusion, recurrent inguinal hernia can occur due to persistent risk factors, and surgical treatment with mesh insertion is an effective definitive therapy to prevent further complications.